Pengaruh Ekuitas Merek dan Promosi terhadap Keputusan Pembelian Air Minum dalam Kemasan Merek Aicos di Padang Pariaman - Henryanto Abaharis; Anggi Aldwi (JURNAL PUNDI, 2020)
Associated with an incraese in the bnottled drinking water industry, through changes to various drinking warer products issued in Padang Pariaman, causing increasingly fierce competition betwen producers. This study to aims to discuss the influence of brands and promotions on purchasing decision of bottled drinking water (AMDK) Aicos brands.This research uses quantitative research methods with a sample of 84 sample of sales data. The analytical method used is multiple linear regressios. The results obtained from this study were Y= 0.204 X1 + 0.461 X2. The result showed that promotion has the greatest.Participation compared to other independent and Promotional variabel on purchasing decisions.The results of study showed a positive and singification ownership variable on purchasing decision.Keywords: Equity, Promotion and Purchasing Decisions